2012
DOI: 10.1111/j.2042-7158.2012.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-inclusion complexes between riboflavin and cyclodextrins

Abstract: The interaction between RF and either βCD or HPβCD, at low concentrations, seems to be made through hydrogen bonding between the flavonoid and the external rim of both CDs. Regardless of the mechanism of complexation, our findings indicate that RF-CD complexes significantly increase RF solubility and potentiate its antitumour effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
(104 reference statements)
2
27
0
1
Order By: Relevance
“…The formation of noninclusion complexes among chemical compounds and cyclodextrins was already reported for other systems, such as for erythromycin 29 and riboflavin. 41 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The formation of noninclusion complexes among chemical compounds and cyclodextrins was already reported for other systems, such as for erythromycin 29 and riboflavin. 41 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Different types of cyclodextrins have been studied for complexation with RF to achieve its stabilization [111117]. In a comparative study of complexation between α- and β-cyclodextrins with RF, β-cyclodextrin was found to form more stable inclusion complexes with RF [116].…”
Section: Reviewmentioning
confidence: 99%
“…Such β-cyclodextrin complexes are suitable for fluorescent compounds for which the fluorescence intensity is influenced by the presence of cyclodextrins [113]. A non-inclusion complexation between RF and β-cyclodextrin or hydroxypropyl-β-cyclodextrin at low concentrations occurred through hydrogen bonding and resulted in a better solubility of RF along with an enhanced antitumor activity [117]. On the contrary, the formation of inclusion complexes between RF and hydroxypropylated α-, β-, and γ-cyclodextrins showed no stabilization effect towards RF.…”
Section: Reviewmentioning
confidence: 99%
“…In the UVX corneas, the anterior stroma at both timepoints and intermediate stroma in the first month did not produce a significantly bigger average SHG than the control stroma and even less in the first month UVX. A likely reason for the lower signal in UVX is the non-zero one-photon absorption value of riboflavin at 400 nm, 50 which attenuates the total SHG signal. The calculated attenuation immediately after riboflavin installation, based on an average concentration of 3.79 mM and average path length of 175 µm, is approximately 44%.…”
Section: Discussionmentioning
confidence: 99%